MODEL PEMBELAJARAN IPS BERBASIS CASE METHOD DALAM MENINGKATKAN PEDAGOGI KRITIS PESERTA DIDIK - Hasni, Hasni; Supriatna, Nana; Sapriya, Sapriya; Winari, Murdiyah; Nur, Muhammad (Universitas Negeri Makassar, 2024)
The learning model has a central role in the learning process of students and requires a touch of teacher creativity pedagogy in developing learning. The purpose of this study is to examine the application of the cash method-based social studies learning model as an effort to improve the critical pedagogy of students, and to determine the advantages of the cash method-based social studies learning model in improving the critical pedagogy of students. The research method used is the library research method by involving searching, researching and analyzing literature relevant to the research. Data analysis techniques use a content analysis model with steps to determine the design, search for basic data, and search for consequential knowledge. The results showed that the application of the case method-based social studies learning model as an effort to improve the critical pedagogy of students in junior high school was carried out by social studies teachers with three stages being the organization stage, group work, evaluation and the awarding stage. The advantages of the case method model are: training analytical and problem-solving skills, improving critical thinking skills, collobirative learning, helping to link theory with practice and developing communication skills. This research is expected to be the basis for social studies teachers in developing students' critical pedagogy in real terms and providing opportunities to improve students' skills, namely creative skills, critical thinking skills, communication skills, dan collaboration skills.